(untitled) (Journal of Solar Energy Research Updates, 2022)
Abstract: The paper considers small solar installations, which are developed and created at the Institute of Materials Science of the Academy of Sciences of the Republic of Uzbekistan. The authors of the article operate a Large Solar Furnace with a thermal power of 1000 kW and have extensive experience in operating and building solar high-temperature furnaces. Small solar installations are simple, cheap and easy to operate.